The Construction of turn taking and interactional moves pragmatics analysis in drama Tarling Cirebon - Dede Rosyadi ZA (Concept : Community Concern for English Pedagogy and Teaching, 2022)
This study examines how turn construction talks and the conversational interaction movements that have been distributed by Cirebon Tarling drama actors that are in the form of conversation. Analysis of identity, motivation, and ideology complements this analysis to identify identity, motivation, and ideology which are the backgrounds for the turn construction of speech and the movement of conversation interactions. Data was obtained from two sources, namely first, the Cirebon Tarling drama entitled “Gila Harta Warisan” and “Mencari Wali Sejati”. The initial data is in the form of video. Then the researcher listens and looks at it and changes it into a conversation transcript. The method that used is descriptive method. Techniques used through transcription, recording, collection, reduction, and analyzing. The results of the study show the following: Identified turn taking construction and the construction of interactional moves in the Cirebon regional languages ??are not much different from English. It was identified that there were participants who started the conversation with small talk or older siblings. A person's identity plays an important role in acting speech. Identity influences the speech of the speaker. Motivation is the impulse of someone in acting well or acting in speech. In this study motivation becomes a person's background in speaking. Ideology is a person's principle in acting behavior and acting speech. The relation between the identity, motivation, and ideology of participants is very related. keywords: turn taking; interactional moves; identity; motivation; ideology.